PENGARUH MODEL PEMBELAJARAN STUDENTS TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS III SD NEGERI 42 PALEMBANG - Bibiana Bribin (Universitas Katolik Musi Charitas, 2019)
This research aimed to identify the influence of learning model by using Students Teams Achievement Division (STAD) toward the result of Mathematic study. This research was True Experimental Design with Posttest-Only Control Design. The sample of this research were third graders A and B of SD Negeri 2 Palembang in 2018/2019 with the total students were 54 students.The instruments that were used in this research were questions in essay form (cognitive),validity test for questions, and reliability for questions. The data of study results were from posttest. The result of posttest was tested with normality test, homogeneity test, hypoheses test by using t-test and the significant value was 0.05. The sum of posttest score in experiment group was 67.19 meanwhile in control group was 55.21. Based on the result of hypotheses test it could be known that tcount ttablethat was13,02 1,676therefore it could be concluded that there is influence of learning model by using Students Teams Achievement Divison (STAD) toward the result of Mathematic study of third graders in SD Negeri 2 Palembang.